P3.435 Opt-Out Rectal Screening For Chlamydia and Gonorrhea in Young Men Who Have Sex with Men (YMSM). (13th July 2013) - Hart-Cooper, G; Owusu-Edusei, K; Chesson, H; Hoover, K
Abstract : Objective: In the United States, almost 20% of new HIV infections in 2010 occurred in young MSM (YMSM) aged 13–24 years old. YMSM also have high rates of other sexually transmitted infections (STIs). STIs can facilitate HIV transmission and acquisition, and indicate unsafe sexual behaviour that might be conducive to HIV transmission. CDC recommends risk-based rectal chlamydia and gonorrhoea screening of MSM who report receptive anal intercourse (RAI), to protect their health and prevent HIV transmission. However, screening rates have been low. Opt-out screening of all YMSM during clinical encounters might be an effective approach to STI screening. Methods: We used a cohort decision analysis model to compare two screening algorithms of YMSM aged 18–24 years: (1) risk-based screening of YMSM who report RAI, and (2) screening YMSM unless they opt-out. Based on published data, we assumed that 61% of YMSM disclosed same-sex behaviour to providers and that 67% of YMSM had RAI. Among YMSM who had RAI, 16% underwent risk-based rectal screening for chlamydia and/or gonorrhoea, and the prevalence of infection was 12%. Outcomes included the number of rectal infections identified and number of tests required to identify one infection. Results: Among 1000 YMSM, opt-out screening identified 59% of infections versus 16% with risk-based screening. Opt-out screening required 10.4 tests to identify one infection versus 8.4 with risk-based screening. Both screening approaches missed 39% of infections because providers were unaware that patients were MSM. Conclusions: Although opt-out screening required two additional tests to identify one case, it identified 3.7 times more infections. Increased diagnosis and treatment of STIs can lead to decreased STI prevalence and HIV transmission, facilitate provider interventions for at-risk youth, and increase patient awareness of the risks associated with unsafe sexual practises. Increased awareness of patients' sexual behaviour among providers is needed to provide optimal care.